(untitled) (Jurnal Ilmiah Teknik Sipil, 2026)
This study is aimed to examine thoroughly lontar Asta Kosala Kosali and Asta Bumi in regard to ashta or eight sectors of geometric pattern as devoted to Dewata Nawa Sangha. Several Balinese homes are studied especially during ritual ceremony yadnya as empirical field work, in order to combine with textual lontar content. Lontar asta kosala kosali describe that the four sides of the proposed home yard required to be divided by nine in the same size section. This technic will draw one square in the center and eight surrounding squares and provide the most practical way to draw eight surrounding sectors in a circle. Any space or point in any eight sectors in the space pattern will be located easily by constructing longitude and latitude across the center. This study revealed that this technic may establish various number of lay-out, resulting in space thrifty that promote psychological well-being thrive happy, calm, no angry in designing Balinese home in pursuing Dewata Nawa Sangha and the teaching of dharma ning asta kosala kosali and asta bumi.